2009
DOI: 10.2355/isijinternational.49.1051
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations in Ce–Al–Fe–S Based Grain Refiners for Steels

Abstract: In the present investigation the phase relations within the Ce-Al-Fe-S system have been clarified, using a combination of optical microscopy and WDS microprobe analyses. As a starting point high-purity charge materials of cerium, aluminium and FeS 2 are melted and superheated to about 2 000°C within small tantalum crucibles inside a dedicated laboratory furnace filled with cleaned argon. The phases detected in the assolidified samples were CeS, Ce 3 Al, Fe 2 Ce and g-Ce, along with Ce 2 O 2 S, which is an unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[1][2][3][4] The steels can solidify with a well-refined equiaxed structure with sufficient additions of TiN particles. There are important technological and fundamental physical reasons for an increased understanding of heterogeneous nucleation mechanism of delta iron on the TiN substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The steels can solidify with a well-refined equiaxed structure with sufficient additions of TiN particles. There are important technological and fundamental physical reasons for an increased understanding of heterogeneous nucleation mechanism of delta iron on the TiN substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that CeS-based grain refiners can be produced from high-purity charge materials of Ce, Al and FeS 2 (pyrite), which are melted and superheated to about 2 000°C in tantalum crucibles under the shield of cleaned argon. 26) However, in order to prevent cerium from oxidising due care must be taken to restrict the supply of oxygen from the surrounding gas atmosphere during manufacturing. The phases observed within the assolidified samples are CeS, Ce 3 Al, Fe 2 Ce and Ce, along with Ce 2 O 2 S, which is an undesirable microconstituent in the grain refiners.…”
Section: Introductionmentioning
confidence: 99%
“…26) In the present investigation, attempts will be made to produce the CeS-based grain refiners without adding iron by using Ce 2 S 3 as the sulphur source. According to the binary Ce-S phase diagram the solubility of sulphur in liquid cerium at 2 000°C should be of the order of 10 wt%, 25) which is formidable compared to that inferred from other potential systems like Fe-Mn-S and Dy-S but more similar to that of La-S. 25,27) Although between 2 and 5 wt% of aluminium is needed to improve the long-term stability of the grain refiners in contact with air by promoting the Ce 3 Al compound formation, 26) such small aluminium additions would not be expected to impose large restrictions on the sulphur solubility. Still, this needs to be verified experimentally by carrying out a series of exploratory measurements of the phase relations within the ternary Ce-S-Al system.…”
Section: Introductionmentioning
confidence: 99%
“…This type of CeS dispersed alloy has also been produced with a matrix of Ce-aluminides. 34,35) 3.2. Development of Ti-oxide/Nitride Based Grain Refiners for Steels As stated earlier Ti-oxides and Ti-nitrides can have a profound influence on the microstructure.…”
Section: Development Of New Ces-based Grain Refinersmentioning
confidence: 99%